MBRS-35. COMBINING Chk1/2 INHIBITION WITH RADIATION ENHANCES IN VITRO AND IN VIVO CYTOTOXICITY IN MEDULLOBLASTOMA. Issue 2 (22nd June 2018) - Endersby, Raelene; Hii, Hilary; Strowger, Brooke; Dyer, Patrick; Howlett, Meegan; Kuchibhotla, Mani; Gottardo, Nicholas
Abstract: Medulloblastoma is a heterogeneous disease, comprising four molecular subgroups, termed WNT, SHH, Group 3 and Group 4. Each has distinct clinical, pathological, and molecular features. Surgical resection and craniospinal irradiation followed by chemotherapy are the mainstay of medulloblastoma treatment. Despite treatment intensification, survival has plateaued for the past two decades at around 70%. Certain sub-groups, namely those with SHH with p53 mutations and Group 3 with MYC amplification, have dismal prognoses. Since medulloblastoma patients that relapse are essentially incurable, ergo, the best opportunity to cure medulloblastoma is during frontline therapy. To increase cure rates, we employed an unbiased high-throughput drug screening approach, to identify novel drugs that enhance the effects of current treatments to aid front-line therapy. We identified prexasertib, an inhibitor of the cell cycle checkpoint kinases 1 and 2 (Chk1/2), as a promising candidate. Chk1/2 are critical regulators of the DNA-damage response. Given radiation is a potent inducer of DNA damage, we hypothesised that Chk1/2 inhibition with prexasertib may enhance radiation-induced cytotoxicity in medulloblastoma. In this study, we found that radiation induced a strong DNA damage response in multiple medulloblastoma models. In vitro, prexasertib reduced the colony-forming ability of medulloblastoma cells post-irradiation. In vivo, tumour-targeted radiation therapy and prexasertib each induced modest apoptosis in orthotopically-implanted medulloblastomas, which was significantly increased when co-administered. Importantly, this combination therapy also improved the survival of mice with medulloblastoma. Taken together, these data reveal significant anti-tumour effects when radiation is combined with Chk1/2 inhibition suggesting that this combination therapy may increase treatment efficacy.